Interproximal Enamel Reduction in Orthodontics - Derya Germeç; Tülin Uğur-Taner (Galenos Yayinevi, 2008)
Interproximal enamel reduction (stripping) is a procedure to remove proximal enamel with the use of various instruments and techniques. In orthodontic practice, interproximal reduction has been widely used for years. The aim of this review is to introduce several enamel reduction techniques and materials, to inform their indications and to give clinical suggestions to the orthodontists.